Integrated Microbiomic and Metabolomic Dynamics of Fermented Corn and Soybean By-Product Mixed Substrate - Wang, Cheng; Wei, Siyu; Jin, Mingliang; Liu, Bojing; Yue, Min; Wang, Yizhen (Frontiers in Nutrition, 2022)
Microbes and their metabolites produced in fermented food have been considered as critical contributors to the quality of the final products, but the comprehensive understanding of the microbiomic and metabolomic dynamics in plant-based food during solid-state fermentation remains unclear. Here, the probiotics of Bacillus subtilis and Enterococcus faecalis were inoculated into corn and defatted soybean to achieve the two-stage solid-state fermentation. 16S sequencing and liquid chromatography-tandem mass spectrometry were applied to investigate the dynamics of microbiota, metabolites and their integrated correlations during fermentation. The results showed that the predominant bacteria changed from Streptophyta and Rickettsiales at 0 h to Bacillus and Pseudomonas in aerobic stage and then to Bacillus, Enterococcus, and Pseudomonas in anaerobic stage. Totally 229 notably different metabolites were identified at different fermentation time, and protein degradation, amino acid synthesis and carbohydrate metabolism were the mainly metabolic pathways during the fermentation. Notably, phenylalanine metabolism was the most important metabolic pathway in fermentation process. Further analysis of the correlations among the microbiota, metabolites and physicochemical characteristics indicated that Bacillus spp. was significantly correlated with amino acids and carbohydrate metabolism in aerobic stage and Enterococcus spp. was remarkably associated with amino acids metabolism and lactic acid production in anaerobic stage. The present study provides new insights into the dynamic changes in the metabolism underlying the metabolic and microbial profiles at different fermentation stages, and are expected to be useful for future studies on the quality of fermented plant-based food.